Role of salivary malondialdehyde in assessment of oxidative stress among diabetics - Komal Smriti; Keerthilatha Muralidhar Pai; Vineetha Ravindranath; Kalyana Chakravarthy Pentapati (Elsevier, 2016)
Aims: To evaluate and compare the salivary content of malondialdehyde (MDA) in patients with type 2 diabetes and control subjects. Methods: We conducted a cross-sectional study among 30 freshly diagnosed subjects of diabetes mellitus and 30 volunteers with no diabetes mellitus. Serum and salivary MDS levels were evaluated among all the subjects. Results: The mean serum MDA in group controls and diabetics was 0.95 ± 0.13 and 3.11 ± 0.42. The mean salivary MDA in group controls and diabetics was 0.26 ± 0.05 μmol/l and 0.81 ± 0.07 μmol/l. The mean serum and salivary MDA levels were significantly higher in group diabetics than control group (p < 0.001 and <0.001) respectively. There was significant positive strong correlation between serum and salivary MDA levels in both controls and diabetics groups (r = 0.857, p < 0.001 and r = 0.891, p < 0.001) respectively. Conclusion: MDA was detectable in saliva in both diabetic and control groups. There was a positive significant correlation between salivary and serum MDA in diabetic and control subjects. Hence, salivary MDA appears to be an indicator of serum MDA concentration.